EIF4A2 as another novel fusion partner of PLAG1 in lipoblastoma - Rofieda R. Alwaqfi; Jonathan J. Davick; Aaron D. Bossler (Elsevier, 2022)
The 5th edition of the WHO classification of Soft Tissue and Bone tumors recognizes lipoblastoma as a benign adipocytic tumor with excellent prognosis and a recurrence rate of 13-46%. The characteristic genomic alteration that helps separate lipoblastoma from morphologic mimics particularly myxoid liposarcoma is rearrangement of 8q11-13 involving PLAG1. PLAG1 (Pleomorphic adenoma gene 1) is located at 8q12.1 and have been reported to be involved in chromosome rearrangements in various tumors including lipoblastoma, epithelial, and mesenchymal tumors. At least 20 fusion partners of PLAG1 have been reported. This report presents EIF4A2 (Eukaryotic Translation Initiation Factor 4A2) as a novel fusion partner of PLAG1.